Synthesis, DFT, electrochemical, biological and DNA-interaction studies of a novel copper(II) complex of salicylic acid and N-tosyl substituted benzimidazole. Issue 1 (2nd January 2020) - Rashid, Naghmana; Kiran, Almas; Ahmad, Iqbal; Ashraf, Zaman; Mohd. Yamin, Bohari; Rafiq, Muhammad
Abstract: Sulfonylbenzimidazoles and their copper complexes have tremendous applications in drug development. In the present work, bis(2-hydroxylbenzoato-κ 2 O, O′)bis(2-methyl-1-(toluene-4-sulfonyl)-1H-benzimidazole) copper(II) complex [Cu(L1 )(L2 )] has been synthesized and structurally characterized by Fourier-transformed infrared spectroscopy (FTIR) and single-crystal X-ray diffraction (XRD). The complex formed a distorted octahedral geometry with the benzimidazole ligands occupying the axial position and the hydroxylbenzoato ligands in the equatorial positions. The latter ligands coordinated in an isobidentate manner with a Cu–O deprotenated bond length of 1.955(18) Å and a long range Cu–O carbonyl of 2.574(2) Å. An excellent correlation was found between bond lengths and bond angles obtained experimentally from single-crystal XRD analysis and that obtained from density functional theory. Electrochemical behavior of [Cu(L1 )(L2 )] has been probed by cyclic voltammetry (CV). CV studies revealed that it undergoes one-electron reduction followed by one-electron oxidation process. In vitro tyrosinase inhibitory activity of the complex was evaluated and it was observed that it exhibited good inhibitory potential with IC50 value 56.8 ± 11.4 μM. Complex-DNA-interaction studies were performed by CV, electronic and florescence spectroscopic titrations and it has been inferred that the [Cu(L1 )(L2 )] binds with DNA through intercalation and the value of binding constant was 3.6 × 10 4 M −1 . Graphical Abstract: UF0001